Reconfigurable instruction set processors from a hardware - Barat, F.
This paper presents the design alternatives for reconfigurable instruction set processors (RISP) from a hardware/software point of view. Reconfigurable instruction set processors are programmable processors that contain reconfigurable logic in one or more of its functional units. Hardware design of such a type of processors can be split in two main tasks: the design of the reconfigurable logic and the design of the interfacing mechanisms of this logic to the rest of the processor. Among the most important design parameters are: the granularity of the reconfigurable logic, the structure of the configuration memory, the instruction encoding format, and the type of instructions supported. On the software side, code generation tools require new techniques to cope with the reconfigurability of the processor. Aside from traditional techniques, code generation requires the creation and evaluation of new reconfigurable instructions and the selection of instructions to minimize reconfiguration time. The most important design alternative on the software side is the degree of automatization present in the code generation tools.
Keywords: RISP; Code generation tools; Configuration memory; Embedded systems; Hardware design; Hardware software codesign; Instruction encoding format; Microprocessor; Program compiler; Programmable processors; Reconfigurable instruction set processors; Reconfigurable logic